Effectiveness of a behavioural intervention involving regular weighing and feedback by community midwives within routine antenatal care to prevent excessive gestational weight gain: POPS2 randomised controlled trial. Issue 9 (17th September 2019) - Daley, Amanda; Jolly, Kate; Jebb, Susan A; Roalfe, Andrea; Mackilllop, Lucy; Lewis, Amanda; Clifford, Sue; Usman, Muhammad; Ohadike, Corah; Kenyon, Sara; MacArthur, Christine; Aveyard, Paul
Abstract : Objectives: To assess the effectiveness of a brief behavioural intervention based on routine antenatal weighing to prevent excessive gestational weight gain (defined by US Institute of Medicine). Design: Randomised controlled trial. Setting: Antenatal clinic in England. Participants: Women between 10 +0 and 14 +6 weeks gestation, not requiring specialist obstetric care. Interventions: Participants were randomised to usual antenatal care or usual care (UC) plus the intervention. The intervention involved community midwives weighing women at antenatal appointments, setting maximum weight gain limits between appointments and providing brief feedback. Women were encouraged to monitor and record their own weight weekly to assess their progress against the maximum limits set by their midwife. The comparator was usual maternity care. Primary and secondary outcome measures: Excessive gestational weight gain, depression, anxiety and physical activity. Results: Six hundred and fifty-six women from four maternity centres were recruited: 329 women were randomised to the intervention group and 327 to UC. We found no evidence that the intervention decreased excessive gestational weight gain. At 38 weeks gestation, the proportions gaining excessive gestational weight were 27.6% (81/305) versus 28.9% (90/311) (adjusted OR 0.84, 95% CI: 0.53 to 1.33) in the intervention and UC group, respectively. There were no significant difference between the groups in anxiety or depression scores (anxiety: adjusted mean −0.58, 95% CI:−1.25 to –0.8; depression: adjusted mean −0.60, 95% CI:−1.24 to –0.05). There were no significant differences in physical activity scores between the groups. Conclusions: A behavioural intervention delivered by community midwives involving routine weighing throughout pregnancy, setting maximum weight gain targets and encouraging women to weigh themselves each week to check progress did not prevent excessive gestational weight gain. There was no evidence of psychological harm. Trial registration number: ISRCTN67427351